2011
DOI: 10.1002/ijc.25965
|View full text |Cite
|
Sign up to set email alerts
|

Bezielle (BZL101)‐induced oxidative stress damage followed by redistribution of metabolic fluxes in breast cancer cells: A combined proteomic and metabolomic study

Abstract: Bezielle (BZL101)-induced oxidative stress damage followed by redistribution of metabolic fluxes in breast cancer cells: a combined proteomic and metabolomic study Bezielle is an orally administered aqueous extract of Scutellaria barbata for treatment of advanced and metastatic breast cancer. Phase I trials showed promising tolerability and efficacy. In our study, we used a combined proteomic-metabolomic approach to investigate the molecular pathways affected by Bezielle in ER-positive BT474 and ER-negative SK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…Previously published analysis of the transcriptional changes induced by Bezielle in tumor cells [8] indicated that the glutathione redox system is engaged in the cellular response to Bezielle, a conclusion supported by the recent proteomic and metabolomic analyses [24]. Thus, elevated expression of cystathionine-beta-synthase and glutamate cysteine ligase modifier GCLM were observed in Bezielle treated tumor cells but not in non-transformed cells.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Previously published analysis of the transcriptional changes induced by Bezielle in tumor cells [8] indicated that the glutathione redox system is engaged in the cellular response to Bezielle, a conclusion supported by the recent proteomic and metabolomic analyses [24]. Thus, elevated expression of cystathionine-beta-synthase and glutamate cysteine ligase modifier GCLM were observed in Bezielle treated tumor cells but not in non-transformed cells.…”
Section: Resultsmentioning
confidence: 76%
“…Indeed, our results show that Bezielle induces mainly necrotic death [8] that is known to be associated with the hyperactivation of PARP-1 [21], [22], [23]. A recent detailed combined proteomic and metabolomic analysis of breast cancer cells treated with Bezielle revealed induction of oxidative stress damage followed by redistribution of metabolic fluxes [24]. Specifically, three families of enzymes involved in maintenance of redox potential were affected by Bezielle: glutathione- and thioredoxin-related proteins and peroxiredoxins.…”
Section: Introductionmentioning
confidence: 62%
“…Storage at 280°C is the recommended condition for long-term LC-MS/MS-based metabolomic analyses (17) and samples have been shown to be stable across time and freeze thaw cycles with this storage method (18). These technologies are well established in our laboratory (19)(20)(21)(22) and utilize a positive/negative ion switching, targeted mass spectrometry-based metabolomics platform on an AB Sciex 5500 QTRAP system (AB Sciex, Concord, ON, Canada) that was established by Yuan et al (23) and further extended and improved within our laboratory. This method utilizes compound-specific multiple reaction monitoring transitions.…”
Section: Urine Metabolomicsmentioning
confidence: 99%
“…barbata has been most extensively studied for breast cancer treatment, with extensive testing done on five different types of breast cancer cells showing S. barbata extracts had more than 50% inhibition in three out of the five cell lines (Campbell et al, 2002). BZL101 was repeatedly documented to exhibit cytotoxic effects on both ER+ and ER-breast cancer cell lines (Fong et al, 2008;Klawitter et al, 2011;Marconett et al, 2010). Due to strong preclinical data, BZL101…”
Section: Figurementioning
confidence: 99%